Comparative effects of 9-month in-season resistance training with a novel periodization approach (integral periodization) vs. a traditional approach on high-intensity actions and non-contact injuries in young, trained soccer players - Jimenez-Iglesias, Jose; Gonzalo-Skok, Oliver; Landi-Fernández, Mario; Perez-Bey, Alejandro; Pascua-Roca, Eduardo de la; Piqueras, Pedro Gómez; Campos-Vazquez, Miguel Angel; Castro-Piñero, Jose (Biology of Sport, 2025)
The aim of the present study was to examine the effect of a novel periodization model integral periodization (IP) – that considers the load balance between game-specific demands and resistance training sessions and to compare it with the effect a traditional periodization model (TP) of resistance training (RT) on fitness through lower-body muscular strength, acceleration and speed, change of direction ability, and cardiorespiratory fitness performance, in addition to non-contact injury incidence in young, trained soccer players during a full season. Forty-five ( n = 21 vs n = 24) trained soccer players (15.2±0.1 years) were randomly divided into a TP training group (TPG) and an IP training group (IPG). High-intensity actions (HIAs) were evaluated through countermovement jump (CMJ), squat and hip-thrust progressive loading tests, a 10-m and 30-m sprint test, a V-cut test, and a 30–15 intermittent fitness test, and non-contact injuries were recorded. In RT sessions, TPG used exercises without variability that were repeated systematically, while IPG used variable exercises for compensating the load in reference to what was experienced on the pitch. The results showed significant improvements in all tests (ES: 0.42–4.43, all p < 0.05), except the 30–15 ITF (ES: 0.21–0.27, p = 0.114–0.332), in both groups. However, IPG showed significantly better results than TPG in 10-m ( p < 0.001), 30-m sprint ( p < 0.001), V-cut ( p < 0.012), and non-contact injuries incidence ( p < 0.028). In summary, IPG showed greater HIA improvements compared to TP and reduced non-contact injury incidence in young, trained soccer players.